So close, yet so different: Divergences in resource use may help stabilize coexistence of phylogenetically-related species in a megadiverse grassland - Castro, Silvana A.B.; Silveira, Fernando A.O.; Marcato, Mateus S.; Lemos-Filho, José P. (Flora. Morphologie, Geobotanik, Oekophysiologie, 2018)
•Functional divergence (niche partitioning) stabilizes species coexistence.•We assessed trait divergence in species from two microhabitats in campo rupestre.•Species in xeric sites had lower water potential compared to species in mesic sites.•These results support the idea of hydrological niche segregation in campo rupestre.•Differences in water usage strategies help explain segregated species distribution. The functional mechanisms behind species coexistence are important to understand community assembly in heterogeneous, nutrient-poor, and species-rich communities. Here, we studied the water relations and photosynthetic performance in species from contrasting microhabitats in the campo rupestre, a megadiverse montane, fire-prone grassland that establishes on extremely nutrient-impoverished soils in eastern Brazil. Through a phylogenetically-controlled study, we tested the hypotheses that (1) species from xeric microhabitats show a more pronounced decrease in water potential during the dry season compared to species from mesic microhabitats, and (2) stronger water deficits in xeric microhabitats result in higher photoinhibition compared to species from mesic microhabitats. For all 12 Melastomataceae species, we measured pre-dawn and mid-day xylem water potential (ψx), leaf relative water content (RWC), succulence, photosystem II potential quantum yield (Fv/Fm), and light-response curves in both rainy and dry seasons. We found that species from xeric microhabitats consistently had lower values of xylem water potential compared to species from mesic microhabitats. This pattern was also temporally consistent, showing that species from xeric microhabitats had lower xylem water potential in both seasons. No differences were found in RWC and succulence between seasons or microhabitats, despite receiving similar incident light intensities. The photosynthetic variables contributed little to species segregation in the two microhabitats, but species from xeric microhabitats showed lower Fv/Fm at the dry season. These results support the idea of hydrological niche segregation in campo rupestre and suggest that functional divergences and convergences may help stabilizing species coexistence. Therefore, our study adds evidence that differences in water economy strategies also help explain segregated distribution of species along functional gradients (niche partitioning) in the megadiverse campo rupestre.